Engaging Students’ Writing Competency on Metadiscourse Markers Using Donald Trump Presidential Speeches - Rita Suswati; Njaju Jenny Malik (SAGA: Journal of English Language Teaching and Applied Linguistics, 2023)
This study aimed to investigate the implication of Donald Trump Presidential speeches as the teaching material of Metadiscourse Markers (MM) in writing class. It employed a qualitative study of English students after the pandemic situation. The research population consisted of 30 second-year students (male and female) from one selected class of Contextual Written Language Skills (CWLS) in the English Education Department of State University of Medan, Indonesia. The CWLS students’ writing ability was assessed using a questionnaire and Donald Trump Presidential speech transcripts taken from millercenter.org. The study referred to Hyland’s metadiscourse taxonomy (2005) and Lee’s contextual factors in writing (2016). The findings revealed that there was a distinct improvement in CWLS students’ writing ability between males and females on MM. This study also found that methodological variables such as teaching material and instructional design were some of the influencing factors in the learning process of MM using Donald Trump Presidential speeches.